Triptycene tripods for the formation of highly uniform and densely packed self-assembled monolayers with controlled molecular orientation - Ishiwari, Fumitaka; Sauter, Eric; Zharnikov, Michael (Journal of the American Chemical Society, 2019)
When employing self-assembled monolayers (SAMs) for tuning surface and interface properties, organic molecules that enable strong binding to the substrate, large-area structural uniformity, precise alignment of functional groups, and control of their density are highly desirable. To achieve these goals, tripod systems bearing multiple bonding sites have been developed as an alternative to conventional monodentate systems. Bonding of all three sites has, however, hardly been achieved, with the consequence that structural uniformity and orientational order in tripodal SAMs are usually quite poor. To overcome that problem, we designed 1,8,13-trimercaptomethyltriptycene (T1) and 1,8,13-trimercaptotriptycene (T2) as potential tripodal SAM precursors and investigated their adsorption behavior on Au(111) combining several advanced experimental techniques and state-of-the-art theoretical simulations. Both SAMs adopt dense, nested hexagonal structures but differ in their adsorption configurations and structural uniformity. While the T2-based SAM exhibits a low degree of order and noticeable deviation from the desired tripodal anchoring, all three anchoring groups of T1 are equally bonded to the surface as thiolates, resulting in an almost upright orientation of the benzene rings and large-area structural uniformity. These superior properties are attributed to the effect of conformationally flexible methylene linkers at the anchoring groups, absent in the case of T2. Both SAMs display interesting electronic properties, and, bearing in mind that the triptycene framework can be functionalized by tail groups in various positions and with high degree of alignment, especially T1 appears as an ideal docking platform for complex and highly functional molecular films.